Development of a behaviorally-based pest management strategy for Eucosma giganteana - Scribner, Hazel Fae (My University, 2024)
Eucosma giganteana (Riley) (Lepidoptera: Tortricidae) is a specialist pest of plants within the genus Silphium. Silphium integrifolium Michx. is a perennial oilseed crop native to the prairies of North America. Because of its perenniality, it is touted as a more sustainable alternative to the sunflower systems; however, E. giganteana is a major limiting factor to the domestication and commercialization of this crop. Despite the yearly damage from E. giganteana, there is currently no consistent pest management strategy, rather, the timing of treatment and the treatment type have been highly variable. To have a consistent idea of when to potentially apply a pest management strategy, a growing degree day model can be used. Using this model, the emergence and phenological events of the insect can be accurately predicted in the field and adults can be targeted before they can lay their eggs, thereby effectively disrupting their lifecycle and reducing the density of the larvae that infest flower heads. Timing is only part of what makes a pest control method effective, you also need to know how much a pest population needs to be reduced for a plant to continue to successfully produce. This is known as a damage or economic threshold. Even when a successful pest management program is in place, monitoring pest populations through trapping can provide insight on the current pest populations. Lastly, knowledge of the pest’s response to chemical cues within its environment can help inform what types of pest management will be effective against the pest. My project aimed to address these different aspects of developing a pest management strategy for E. giganteana. Firstly, I address my first objective: to review and synthesize the state of mating disruption of Lepidoptera (Ch. 1). Then, I cover my second objective: to first link trap captures of E. giganteana to plant vigor and/or pest phenology and growing degree days; and then to develop a trap-based threshold or growing degree day model for E. giganteana to guide its mangement using insecticides (Ch. 2). Finally, I go over the studies pertaining to my third objective: to explore the physiological response of E. giganteana to common attractants and S. integrifolium (Ch. 4); to elucidate the flight capacity of E. giganteana and its behavioral response to attractants (Ch. 4); to examine the field response of E. giganteana to increasing concentrations of (E)-8dodecenyl acetate (Ch. 3); and to determine headspace emissions from conspecific moths and S. integrifolium (Ch. 4). By using Ethovision software to quantify the distance moved in millimeters of E. giganteana larvae that were subjected to different acclimation and test temperatures, I determined that their lower activity threshold was approximately 17 °C. The lower activity threshold coupled with localized weather data was used to create a growing degree day model. Field trapping of E. giganteana in 2023 and 2024 as well as previously collected data from 2019 and 2020 were used to determine the degree day measures for specific adult E. giganteana phenological events. With the 2019 data functioning as the predicted degree day measurements and the following three years functioning as the actual degree day measurements for the same phenological events, I found that the degree day model did successful predict when these events would occur. Unfortunately, I was unable to determine the number of E. giganteana larvae required to cause significant damage to S. integrifolium root crowns, and thereby form a damage threshold. Using a previously documented pheromone attractant, (E)-8-dodecenyl acetate, at different concentrations to trap adult E. giganteana, I found that a low concentration was highly effective at monitoring E. giganteana presence when used on its own. However, a 100-fold higher concentration of this attractant will mask the effect of the low concentration. Through examining the antennal responses of both sexes of adult E. giganteana to common semiochemicals within their environment, I found that the sex has an effect on how strongly the moth reacts to the stimulus. I also found that both male and female moths responded to (E)-8-dodecenyl acetate and female E. giganteana headspace which indicates that the females may autodetect their pheromone based on their antennal response. I did not find a difference in the flight propensity and distance flown of adult E. giganteana individuals when in the presence of different concentrations of (E)-8-dodecenyl acetate and the opposite sex moth. Similarly, I did not find a significant difference in the headspace composition collected from males, females, or a 50/50 mix of adult E. giganteana moths. This research is expected to help us better understand the behavior of E. gigantena and guide the timing of pest management within S. integrifolium fields.
Keywords: Growing degree day; Integrated pest management; Pheromone trapping; Giant Eucosma moth; Silphium integrifolium